ANALISIS YURIDIS PUTUSAN NOMOR: 115/PDT.SUS- MEREK/2022/PN.NIAGA. JKT.PST TENTANG SENGKETA MEREK DAGANG KASO DAN KASOMAX - Ruhtiani, Maya; Abrillia, Marcella; Hafny Afrilies, Marlia (J-LEE - Journal of Law, English, and Economics, 2025)
This study examines the trademark dispute between PT Tatalogam Lestari (owner of the "KASO" mark) and Tedi Hartono (registrant of the "kasomax" mark), adjudicated by the Commercial Court of Central Jakarta (Decision No. 115/Pdt.Sus-Merek/2022). The dispute arose from alleged violations of the first-to-file principle, distinctiveness, and bad faith in trademark registration. Indonesia adopts a first-to-file system under Law No. 20 of 2016 concerning Trademarks and Geographical Indications, granting exclusive rights to the first registrant. This case demonstrates that registering marks similar to existing trademarks may cause consumer confusion and unfair competition.The study aims to analyze the court’s legal considerations in the ruling and the application of trademark principles in dispute resolution. A normative juridical approach was employed, utilizing primary legal sources (statutes, court decisions) and secondary materials (literature, journals).Findings indicate the Commercial Court annulled the registration of "kasomax" due to its fundamental similarity to the "KASO" mark and bad-faith registration. The ruling reinforces the first-to-file principle and provides legal certainty for registered trademark owners. The implications suggest the need for stronger substantive examination by the Directorate General of Intellectual Property (DGIP) and public awareness campaigns to prevent infringing registrations.